Mobile Ultrasound Tracking and Magnetic Control for Long‐Distance Endovascular Navigation of Untethered Miniature Robots against Pulsatile Flow. (24th March 2022) - Yang, Lidong; Zhang, Moqiu; Yang, Zhengxin; Yang, Haojin; Zhang, Li
Abstract : Mobile Ultrasound Tracking and Magnetic Control In article number 2100144, Li Zhang and co‐workers propose an innovative combination of eye‐in‐hand ultrasound imaging and mobile‐coil magnetic manipulation system to realize real‐time tracking and navigation of a helical magnetic robot against pulsatile flow. Two novel algorithms that can overcome the US noises and view lost are presented to ensure the tracking stability and accuracy. This method provides a promising approach for microrobot navigation in the vascular system of the human body.